2002
DOI: 10.1136/bmj.324.7346.1129
|View full text |Cite
|
Sign up to set email alerts
|

Safety education of pedestrians for injury prevention: a systematic review of randomised controlled trials

Abstract: Objectives To quantify the effectiveness of safety education of pedestrians. Design Systematic review of randomised controlled trials of safety education programmes for pedestrians of all ages. Main outcome measures Effect of safety education on pedestrians' injuries, behaviour, attitude, and knowledge and on pedestrian-motor vehicle collisions. Quality of trials: methods of randomisation; and numbers lost to follow up Results We identified 15 randomised controlled trials of safety education programmes for ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
0
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 13 publications
3
113
0
13
Order By: Relevance
“…1 Pedestrian-oriented educational measures may change pedestrians behavior when crossing the street, but it is still unknown whether they effectively reduce the risks of motor vehicle-pedestrian collisions. 1 Motor vehicle-pedestrian collisions may occur even under optimal lighting conditions, dry lanes and streets and good weather, but in zones densely populated with children, who lack knowledge and maturity to cross the streets, these accidents are very common; therefore, emphasis should be placed on providing children with a safe place where they can play and be supervised, and only be allowed to cross the streets if they have learned the technique properly. 23,24 Training should begin in preschool, indicating the appropriate and safer places for crossing the street, 24 always considering the childs attention development and highlighting its importance throughout school years.…”
Section: Pedestrian Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…1 Pedestrian-oriented educational measures may change pedestrians behavior when crossing the street, but it is still unknown whether they effectively reduce the risks of motor vehicle-pedestrian collisions. 1 Motor vehicle-pedestrian collisions may occur even under optimal lighting conditions, dry lanes and streets and good weather, but in zones densely populated with children, who lack knowledge and maturity to cross the streets, these accidents are very common; therefore, emphasis should be placed on providing children with a safe place where they can play and be supervised, and only be allowed to cross the streets if they have learned the technique properly. 23,24 Training should begin in preschool, indicating the appropriate and safer places for crossing the street, 24 always considering the childs attention development and highlighting its importance throughout school years.…”
Section: Pedestrian Safetymentioning
confidence: 99%
“…8 Accidents involving a motor vehicle and a child are usually caused by under-forty-year-old male drivers. 18,19 The factors related to a higher risk of motor vehiclepedestrian collisions are: 1,8,17,18 boys, ages 3 to 12 years, number of streets a child has to cross, midblock crossings, daylight hours, school hours, houses without a backyard or recreation area, strong association with alcohol consumption, underprivileged social classes, and unemployment.…”
Section: Pedestrian Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…A hospital-based study of cycling collisions suggested that trained cyclists were three times less likely to be injured whilst cycling than untrained ones 70 . There is evidence that training aimed at increasing pedestrian safety may raise children's level of knowledge of safety issues but this knowledge is subject to decay 131 and actual traffic injury rates were not examined.…”
Section: Cycle Trainingmentioning
confidence: 99%